2006
DOI: 10.1007/s10886-006-9061-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Carbon Dioxide and Ozone on Foliar Proanthocyanidins in Betula platyphylla, Betula ermanii, and Fagus crenata Seedlings

Abstract: Proanthocyanidins (PAs) or condensed tannins are a major group of phenolic compounds in the leaves of birch trees and many other woody and herbaceous plants. These compounds constitute a significant allocation of carbon in leaves and are involved in plant responses to environmental stress factors, such as pathogens or herbivores. In some plants, PA concentrations are affected by atmospheric carbon dioxide (CO(2)) and ozone (O(3)) levels that may influence, for example, species fitness, community structure, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Tannin levels also are influenced by both additive and interactive effects of CO 2 and O 3 . Condensed tannin concentrations responded to the additive, independent effects of CO 2 and O 3 in Fagus crenata and various species of Betula (Kopper et al 2001;Peltonen et al 2005;Karonen et al 2006), but to the interactive effects of CO 2 and O 3 in Populus tremuloides (Holton et al 2003). Similarly, the effects of CO 2 and O 3 on monoterpenes and sesquiterpenes in Pinus sylvestris sometimes were additive and sometimes interactive (Sallas et al 2001).…”
Section: Ozonementioning
confidence: 97%
“…Tannin levels also are influenced by both additive and interactive effects of CO 2 and O 3 . Condensed tannin concentrations responded to the additive, independent effects of CO 2 and O 3 in Fagus crenata and various species of Betula (Kopper et al 2001;Peltonen et al 2005;Karonen et al 2006), but to the interactive effects of CO 2 and O 3 in Populus tremuloides (Holton et al 2003). Similarly, the effects of CO 2 and O 3 on monoterpenes and sesquiterpenes in Pinus sylvestris sometimes were additive and sometimes interactive (Sallas et al 2001).…”
Section: Ozonementioning
confidence: 97%
“…For example, in Populus (Osier and Lindroth, 2006), Salix (Orians et al, 2000), and Betula (Laitinen et al, 2000), the quantity of proanthocyanidin accumulated is genetically determined. Levels of proanthocyanidins in Populus, Salix, Betula, and Fagus are affected by environmental conditions such as levels of light, nutrients, CO 2 , and ozone (Lindroth et al, 2001;Lower and Orians, 2003;Karonen et al, 2006;Osier and Lindroth, 2006). Almost nothing is known about what factors dictate accumulation of specific proanthocyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…Their role in providing protection against UV irradiation (Jaakola et al, 2004) and ozone (Karonen et al, 2006) by decreasing oxidative stress has been demonstrated in numerous plant species. These compounds are also well studied as defenses against mammalian (Theodoridou et al, 2010) and insect herbivory (Feeny, 1970;Donaldson and Lindroth, 2004).…”
mentioning
confidence: 99%